2013
DOI: 10.1590/s1982-56762013005000029
|View full text |Cite
|
Sign up to set email alerts
|

The wild type of Momordica charantia is not infected by potyviruses that cause disease in papaya and cucurbit crops

Abstract: In the present work, the susceptibility of wild and domesticated plants of Momordica charantia to viruses from the genus Potyvirus that cause diseases in papaya (Carica papaya) and cucurbit crops was evaluated. The plants were subjected to experimental and natural infection with Papaya ringspot virus types P and W (PRSV-P and PRSV-W) and Zucchini yellow mosaic virus (ZYMV). None of the potyviruses infected the wild type of M. charantia through mechanical or aphid inoculation or under field exposition, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
2
5
0
1
Order By: Relevance
“…Cucumis anguria is a common weed in Brazilian crops, particularly in papaya orchards, and it has not been related with natural infection of PRSV-P; however, other cucurbits such as Momordica charantia L., and Cucurbita maxima Duchesne cv. Exposição (pumpkin) were not infected by PRSV-P though mechanical or aphid inoculations, and field exposure of plants (Spadotti et al, 2013;Mansilla et al, 2013). These data indicate that these cucurbits species do not seem to have a role in the epidemiology of the papaya ringspot in Brazil.…”
Section: Discussionmentioning
confidence: 77%
“…Cucumis anguria is a common weed in Brazilian crops, particularly in papaya orchards, and it has not been related with natural infection of PRSV-P; however, other cucurbits such as Momordica charantia L., and Cucurbita maxima Duchesne cv. Exposição (pumpkin) were not infected by PRSV-P though mechanical or aphid inoculations, and field exposure of plants (Spadotti et al, 2013;Mansilla et al, 2013). These data indicate that these cucurbits species do not seem to have a role in the epidemiology of the papaya ringspot in Brazil.…”
Section: Discussionmentioning
confidence: 77%
“…In the case of papaya ringspot, only papaya is the principal source of PRSV‐P inoculum. Although this potyvirus can infect some species of Cucurbitaceae, they do not appear to be important in the epidemiology of papaya ringspot (Mansilla et al , ; Spadotti et al , ). In the case of passion flower, there is evidence that the sources of inoculum appear to be mainly the two cultivated species ( P. edulis and P. alata ) and some wild Passiflora species, reported as susceptible to CABMV (Maciel et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…They also identified one Solanaceae species: Solanum americanum. Chin et al (2007) reported that Momordica charantia is a PRSV-P carrier; however, Spadotti et al (2013), after evaluating it through mechanical inoculation and aphid vectors, stated that Momordica charantia is not susceptible to any of the PRSV strains (P and W). In this research, we found a M. charantia specimen from Los Asmoles that appeared healthy and gave negative DAS-ELISA and RT-PCR test results.…”
Section: Identificación De Maleza Y Hospederos Alternos Para Prsvmentioning
confidence: 99%
“…Recientemente, Martins et al (2016), colectaron en Brasil áfidos vectores presentes en 22 especies arvenses de plantaciones de papayo, la mayoría pertenecientes a las familias Euphorbiaceae, Commelinaceae, Brassicaceae y Malvaceae, también se identificó una Solanaceae: Solanum americanum. Chin et al (2007) reportaron a Momordica charantia como portadora de PRSV-P, sin embargo, Spadotti et al (2013) determinaron que ésta especie no es susceptible a ninguna de las cepas de PRSV (P y W), tras evaluar su inoculación mecánica y mediante áfidos vectores en la especie antes mencionada. En este estudio se encontró un ejemplar de M. charantia proveniente de Los Asmoles, el cual tuvo una apariencia sana y presentó un resultado negativo a PRSV por DAS-ELISA y RT-PCR, sin embargo, resulta conveniente analizar en un futuro un mayor número de muestras de esta especie para determinar si puede actuar como reservorio del virus.…”
Section: Identificación De Maleza Y Hospederos Alternos Para Prsvunclassified